A Qualitative Exploration of Shifts to Community Supervision Work During the COVID-19 Pandemic - Lockwood, Ashley (Criminal justice and behavior, 2024)
With the onset of the COVID-19 pandemic, community supervision agencies were forced to incorporate drastic changes to traditional supervision techniques, which shifted the daily roles of probation officers (POs). Research on the pandemic identifies rapid adaptations to supervision strategies and increased demands on POs during the pandemic. Using qualitative data from interviews with POs across the United States, the goal of this study was to examine the experiences of POs working during the COVID-19 pandemic. Results suggest POs had to alter their supervision approach, both physically and ideologically. POs discussed shifts to both remote supervision in place of in-person work coupled with a need to use an “agent of change” approach given limited access to formal, punitive responses to noncompliance, with a priority on the highest risk/need clients. Findings suggest several implications for practice, including factors to consider regarding community correction reform efforts in a post-pandemic world.